Peningkatan Hasil Belajar Siswa pada Mata Pelajaran Pendidikan Agama Islam Terkait Materi Shalat Berjamaah Melalui Metode Demonstrasi - Syamsul Qomar; Sodik Budiono; Fitri Yenti (STIKes Ibnu Sina Ajibarang, 2023)
This study aims to improve students' learning outcomes in congregational prayer material through the application of intensive learning models in Islamic Religious Education (PAI). This study is a Classroom Action Research (CAR) conducted in two cycles, with stages of planning, implementation, observation, and reflection. The results of the study showed a significant increase in students' understanding and skills in performing congregational prayers. The impressive model has proven effective in helping students understand the concept and practice of prayer directly. In conclusion, an impressive learning model can improve students' learning outcomes in congregational prayers, as well as increase students' participation and practical skills in PAI learning.